2014
DOI: 10.1016/j.cbpra.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Informed Guilt Reduction Therapy With Combat Veterans

Abstract: Guilt related to combat trauma is highly prevalent among veterans returning from Iraq and Afghanistan. Trauma-related guilt has been associated with increased risk for posttraumatic psychopathology and poorer response to treatment. Trauma Informed Guilt Reduction (TrIGR) therapy is a 4-module cognitive-behavioral psychotherapy designed to reduce guilt related to combat trauma. The goals of this study were to describe the key elements of TrIGR and report results of a pilot study with 10 recently deployed combat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 62 publications
(100 reference statements)
3
79
0
1
Order By: Relevance
“…Nonetheless, this initial finding is consistent with previous studies of veterans that have highlighted the role of guilt and responsibility, including guilt specifically associated with the loss of a combat buddy, highlighting the special bonds formed within units as well as the relationship of those in decision‐making roles to those who may die in service (Fontana et al, ; Lee, Scragg, & Turner, ; Litz et al, ; Milgram, ; Nazarov et al, ). These considerations have become more widely recognized in PTSD treatments as well as highlighted as an aspect of moral injury, which was not assessed in this study (Litz et al, ; Nazarov et al, ; Norman, Wilkins, Myers, & Allard, ; Øktedalen, Hoffart, & Langkaas, ; Steenkamp et al, ). Further, guilt has also been linked to increased suicidal ideation, particularly among those with direct combat exposure (Bryan, Ray‐Sannerud, Morrow, & Etienne, ).…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, this initial finding is consistent with previous studies of veterans that have highlighted the role of guilt and responsibility, including guilt specifically associated with the loss of a combat buddy, highlighting the special bonds formed within units as well as the relationship of those in decision‐making roles to those who may die in service (Fontana et al, ; Lee, Scragg, & Turner, ; Litz et al, ; Milgram, ; Nazarov et al, ). These considerations have become more widely recognized in PTSD treatments as well as highlighted as an aspect of moral injury, which was not assessed in this study (Litz et al, ; Nazarov et al, ; Norman, Wilkins, Myers, & Allard, ; Øktedalen, Hoffart, & Langkaas, ; Steenkamp et al, ). Further, guilt has also been linked to increased suicidal ideation, particularly among those with direct combat exposure (Bryan, Ray‐Sannerud, Morrow, & Etienne, ).…”
Section: Discussionmentioning
confidence: 93%
“…Session content was not analyzed to understand whether guilt cognitions were addressed. One recent pilot study of an intervention specifically targeting maladaptive guilt in combat veterans showed promise in reducing guilt cognitions and distress (Norman et al., ). It may be that addressing guilt cognitions is an important piece to reducing posttraumatic symptoms when trauma‐related guilt is present.…”
Section: Discussionmentioning
confidence: 99%
“…One trauma‐related guilt conceptualization that has received attention in the literature (e.g., Norman et al., ; Resick et al., ) is the multidimensional construct put forth by Kubany and Watson (), referred to here as the components of posttraumatic guilt model (Figure ). In this model, Kubany and Watson () suggest that trauma‐related guilt is composed of interacting guilt cognitions, distress, and global posttraumatic guilt components.…”
mentioning
confidence: 99%
“…While results from this study may not be generalizable to other Veterans with moral injury who have completed an EBP for PTSD, these findings support the discussion of moral injury in the context of VA care and that some Veterans still experience difficulties with moral injury following EBPs for PTSD. The results of this study suggest the importance of developing inventions that explicitly target moral injury among warzone Veterans (Borges, ; Farnsworth et al, ; Gray et al, ; Maguen et al, ; Norman, Wilkins, Myers, & Allard, ).…”
Section: Resultsmentioning
confidence: 80%